Clinical characteristics and outcomes of traditional Chinese medicine-induced liver injury: a systematic review. (3rd April 2018) - Wang, Ran; Qi, Xingshun; Yoshida, Eric M.; Méndez-Sánchez, Nahum; Teschke, Rolf; Sun, Mingyu; Liu, Xu; Su, Chunping; Deng, Jiao; Deng, Han; Hou, Feifei; Guo, Xiaozhong
ABSTRACT: Backgrounds: Traditional Chinese medicine (TCM) is becoming increasingly popular and related adverse events are often ignored or underestimated. Aims: This systematic review aimed to evaluate the clinical characteristics and outcomes of TCM-induced liver injury (TCM-ILI) and to estimate the proportion of TCM-ILI in all drug-induced liver injuries (DILI). Methods: China National Knowledge Infrastructure, Wanfang, VIP, PubMed, and Embase databases were searched. Demographic, clinical, and survival data were extracted and pooled. Factors associated with worse outcomes were calculated. For the proportion meta-analyses, the data were pooled by using a random-effects model. Results: Overall, 21, 027 articles were retrieved, of which 625 were finally included. There was a predominance of female and older patients. The proportion of liver transplantation was 2.18% (7/321). The mortality was 4.67% (15/321). Male, higher aspartate aminotransferase and direct bilirubin, and lower albumin were significantly associated with an increased risk of death/liver transplantation in TCM-ILI patients. The proportion of TCM-ILI in all DILI was 25.71%. The proportion was gradually increased with year. Conclusions: Our work summarises current knowledge regarding clinical presentation, disease course, and prognosis of TCM-ILI. TCM can result in hepatotoxicity, even death or necessitate life-saving liver transplantation. Governmental regulation of TCM products should be strictly established.